2020
DOI: 10.1155/2020/9071624
|View full text |Cite|
|
Sign up to set email alerts
|

A Hierarchical Attention Recommender System Based on Cross-Domain Social Networks

Abstract: Search engines and recommendation systems are an essential means of solving information overload, and recommendation algorithms are the core of recommendation systems. Recently, the recommendation algorithm of graph neural network based on social network has greatly improved the quality of the recommendation system. However, these methods paid far too little attention to the heterogeneity of social networks. Indeed, ignoring the heterogeneity of connections between users and interactions between users and item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This system utilized user behavior information from social networks and integrated information from heterogeneous human networks. The research results indicated that this system can effectively improve recommendation systems and networks flexibility [7]. Zhu G designed a neural attention travel package recommendation system based on long and short term behavior to address current travel package recommendations not effectively meeting user preferences.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This system utilized user behavior information from social networks and integrated information from heterogeneous human networks. The research results indicated that this system can effectively improve recommendation systems and networks flexibility [7]. Zhu G designed a neural attention travel package recommendation system based on long and short term behavior to address current travel package recommendations not effectively meeting user preferences.…”
Section: Related Workmentioning
confidence: 99%
“…Neighborhood nodes are a collection of users who care about each other, that is, users and their friend pairs. For all users i u and user friend ( ) , i j u , the embedding vector is obtained by combining the gated network, and the expression for the embedding representation is shown in equation (7).…”
Section: B Graph Neural Network Algorithm Integrating Multi Head Atte...mentioning
confidence: 99%
“…Cao et al [22] input the text features into the RCNN (region CNN) neural network model composed of RNN and CNN and applied them to text classification, and the classification performance is improved obviously. Zhao et al [23] proposed a DL model composed of CNN and LSTM based on attention (CLA) by repeated series of convolutional layers and circulation layer. Firstly, the word coding was implemented in series; secondly, they implemented it to realize the sentence coding, and finally, the implicit emotion analysis task was realized at the last layer using the softmax function, based on attention mechanism.…”
mentioning
confidence: 99%